GREATER ZAB RIVER BASIN PLANNING (2050) - Sharef, A. J.; Dara, R. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This research was aimed to study the management of water resources within international basins, among which is the study of water authorities within the Greater Zab River Basin (GZRB) in the Kurdistan region - Iraq, where it is an international river shared by Iraq and Turkey, and aims to develop the river basin management and international cooperation between the authorities Shared water within the basin, as well as identifying factors that affect implementation, the principles, and joint projects. On the other hand, the interactions of water users competing for water inside the river basin were identified. For this reason, the Water Evaluation Analysis Planning (WEAP) model was applied to the basin to determine the optimal GZR planning system and plan optimum operating policy. The main issue with this planning is how the system meets future water needs. For this reason, optimal monthly water distribution policies have been simulated using the WEAP model using the past 33 years’ debt, and the revaluated GZRB performance. An ideal simulation scheme has been developed and implemented for different scenarios such as domestic needs, irrigation water, and ecological water. This study compared to the official figures in the planning work that took place in the eighties. As a result of these comparisons, the average annual water supply was 368.1 million cubic meters in August 2032. Accordingly, it was proposed that the construction of the Bekhme Dam was completed because it understood that the water requirements could not be met in the current conditions.